When method matters : toward a resolution of the debate about Bangladesh's poverty measures - Ravallion, Martin; Sen, Binayak (Washington, D.C. : World Bank, Policy Research Dept., Poverty and Human Resources Division, 1994)
This paper reviews the methodical issues in the debate over whether poverty measures for urban and rural areas using for comparable and nationally representative surveys spanning from the period 1983 to 1992
"September 1994"--Cover.
Includes bibliographical references (p. 31-34).
osa
Ref.
Keywords: Poverty; Bangladesh